O cierpliwości w powieści "Il colibri" Sandra Veronesiego - Janusz, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The present article examines the notion of patience as the narrative axis in Sandro Veronesi`s novel "Il colibri" (2019). Defined as one of the so-called "post-cognitive emotions", patience is axiologically charged and results from the processes of valuing reality and assuming an attitude to it which lead to the formation of a stable stance by the subject. Veronesi constructs the value system of his protagonist by juxtaposing an attitude of patient endurance despite adversities and prevalent ethical stance that promotes changeability and lability of attitudes and beliefs. The author indicates that the meaning of life and the essence of personal identity are linked to the good that exists beyond the individual him- or herself.
Keywords: emocje; cierpliwość; aksjologia; Veronesi, Sandro (włoski pisarz; 1959- ); emotions; patience; axiology